International Conflict, International Security Environment, and Military Coups. Issue 5 (3rd September 2018) - Kim, Nam Kyu
ABSTRACT: Why do some countries repeatedly experience military coups while others seem immune? Are countries more prone to military coups when faced with external threats? The answers to these questions still remain contested: While several scholars hold that countries facing external threats are more vulnerable to coups, others argue that such countries are actually more secure from coups. I argue that by failing to distinguish between immediate and acute threats, caused by wars and militarized conflicts, and chronic threats from a state's international security environment, the existing literature ignores the possibility that these two types of external threats differently affect the likelihood of coups. I propose that wars and militarized conflicts, infrequent and often short lived, decrease coup propensity, while a threatening security environment increases coup risk. I find strong supporting evidence that the presence of chronic international threats increases the likelihood of coups while acute international conflicts lower that likelihood.